ADVANCED POWER TRANSMISSION TECHNIQUES FOR REDUCING LOSSES IN LONG-DISTANCE POWER TRANSFER - Samuel,Batet , Ochogwu Emmanuel Bamaiyi. (My University, 2024)
Power losses in long-distance transmission remain a major challenge for efficient electricity delivery, especially in developing countries like Nigeria. These losses, caused by technical inefficiencies and outdated infrastructure, result in high operational costs, reduced utility revenue, and limited energy access. This study explores advanced transmission techniques—such as High Voltage Direct Current (HVDC),Flexible AC Transmission Systems (FACTS), High Temperature Low-Sag (HTLS) conductors, and Dynamic Line Rating (DLR)—to reduce losses and improve grid reliability. Focusing on the Nigerian power system, the research highlights the economic, social, and environmental impacts of transmission inefficiencies. It demonstrates that adopting modern technologies, coupled with policy reform and strategic investment, can significantly reduce losses, enhance grid performance, and support national development goals.
ADVANCED POWER TRANSMISSION TECHNIQUES FOR REDUCING LOSSES IN LONG-DISTANCE POWER TRANSFER
Keywords: Power losses; transmission efficiency; HVDC; FACTS; Nigeria; grid modernization; smart grid